A Analysis of Logistics Cost Structure in The Clove Supply Chain in Wonosalam District Jombang Recency - Nasywa Aulia Wijaya; Taufik Setyadi; Dita Atasa (JURNAL AGRICA, 2026)
Cloves are a strategic plantation commodity that plays an important role in the economy of farmers and downstream industries. However, high logistics costs and long supply chains have the potential to reduce the profits received by farmers. This study aims to analyze the supply chain flow, logistics cost structure, and profit distribution in the clove supply chain in Wonosalam District, Jombang Regency. The research method uses a quantitative descriptive approach with the application of Activity-Based Costing (ABC). Data were obtained from 30 farmers, 6 collectors, and 3 wholesalers through interviews and field observations. The results show that logistics costs at the farmer tier are dominated by material handling activities at 82.03%, while at the collector and wholesaler tiers, they are dominated by procurement at 99.36% and 99.43%, respectively. Profit distribution in the supply chain is uneven, with farmers selling cloves at Rp105,800/kg, while wholesalers earn the highest marketing margin of Rp11,000/kg. The farmer's share value of 85.81% shows that although the supply chain is relatively efficient, the burden of logistics costs is still concentrated at the farmer level. Therefore, logistics efficiency strategies and government policy support are needed to improve the sustainability of the clove supply chain